Argonaute2 and Argonaute4 Involved in the Pathogenesis of Kawasaki Disease via mRNA Expression Profiles - Zon-Min Lee; Hui-Chuan Chang; Shih-Feng Liu; Ying-Hsien Huang; Ho-Chang Kuo (Children)
Background: Argonautes (AGOs) are a type of protein that degrade specific messenger RNAs, consequently reducing the expression of a specific gene. These proteins consist of small, single-stranded RNA or DNA and may provide a route for detecting and silencing complementary mobile genetic elements. In this research, we investigated which AGO(s) were involved in Kawasaki disease (KD). Methods and Materials: We obtained mRNA-level gene expression profiles from leukocyte samples that had previously been gathered in another study and uploaded to the NCBI GEO database. The Human Transcriptome Array (HTA 2.0) analysis included 50 children with KD prior to IVIG (KD1), 18 children with KD three weeks post-IVIG (KD3), 18 non-febrile controls (HC), and 18 febrile controls (FC), which were arranged in the quoted publications for all materials and methods in order to collect data. We used the default value of the commercialized microarray tool Partek to perform an analysis of variance and determine any significant fold changes (KD1, KD3, HC, and FC individually). Results: The data revealed that the AGO2 and AGO4 genes displayed significant within-group differences with p = 0.034 and 0.007, respectively. In AGO2, significant differences were observed between KD1 vs. HC + FC with p = 0.034. KD1 appears higher than the other specimens in AGO4, with significant differences between KD1 and HC (p = 0.033), KD1 and FC (p = 0.033), KD1 and KD3 (p = 0.013), and KD1 and HC + FC (p = 0.007). We observed no substantial differences in AGO1 or AGO3 (p > 0.05). There were no significant differences between AGO(s) and coronary artery lesions or intravenous immunoglobulin resistance. (p > 0.05) Conclusion: Endothelial cell inflammation and injury, two basic pathological mechanisms, are thought to be involved in coronary endothelial dysfunction in KD. AGO2 and AGO4 are likely to participate in the endothelial dysfunction of children with KD, with AGO4 potentially playing a key role, while AGO1 and AGO3 appear not to participate.